1979
DOI: 10.1136/thx.34.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture on lung volume: airway closure and gas exchange in hemidiaphragmatic paralysis.

Abstract: The effects of posture on lung volume, airway closure, and gas exchange were studied in eight patients with hemidiaphragmatic paralysis. The mean vital capacity in the sitting position was 81% of predicted normal, and in the supine posture fell by a further 19% in right-sided but only 10% in left-sided paralysis. The mean arterial oxygen tension was less than predicted in the sitting posture and fell significantly on lying. Single breath gas transfer factor was normal in all cases whereas the diffusion coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The reduction in VC observed in our patients without concomitant lung disease is similar to those reported by Lisboa et al [4] and greater than those reported by Clague and Hall [3]. The decrease in lung volumes ob served by Gould et al [9] in acute UDP induced by phrenic nerve blockade (14% for VC) was also less than that measured in most of our patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reduction in VC observed in our patients without concomitant lung disease is similar to those reported by Lisboa et al [4] and greater than those reported by Clague and Hall [3]. The decrease in lung volumes ob served by Gould et al [9] in acute UDP induced by phrenic nerve blockade (14% for VC) was also less than that measured in most of our patients.…”
Section: Discussionsupporting
confidence: 89%
“…Laroche et al [14] demonstrated that the mean maximum increment in transcutaneous C 0 2 was within normal limits. Clague and Hall [3] have shown that the closing volume (CV) as a percentage of VC tended to be less than predicted in patients with UDP. Because of the reduction in expiratory reserve volume (ERV), the relationship ERV/CV was much less than predicted, being negative in several patients in the supine position.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A diaphragm paralysis due to phrenicotomy causes decreases in tidal volume and in dynamic lung compliance, and an increase in the work of breathing due to paradoxical movements of the paralysed diaphragm [5][6][7], which may lead to increases in postoperative morbidity and motility. Diaphragm plication is an acceptable treatment for paediatric patients with life-threatening unilateral diaphragm paralysis [8][9][10], while benefits have also been reported in adult patients with chronic unilateral diaphragm paralysis [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, a decrease in FVC of up to 20% may be observed in the supine position when compared with upright values 19 ; in symptomatic patients with diaphragmatic paralysis, supine FVC may decrease by 20 to 50% when compared with upright values. [19][20][21][22] The main value of PFTs in the evaluation of symptomatic patients with hemidiaphragmatic elevation is to provide an objective evaluation of the response to surgery; however, changes in PFT values are variable, are not critical for patient selection, and do not always correlate well with clinical improvement.…”
Section: Pulmonary Function Testsmentioning
confidence: 99%